Editorial : Foot-and-mouth disease epidemiology, vaccines and vaccination : moving forward - Capozzo, Alejandra (2023)
Vaccination has played a major role in foot-and-mouth disease (FMD) control. There are different approaches to the design and implementation of vaccination campaigns, and epidemiological information is paramount in influencing the vaccine and vaccination strategy that best suit each geographic location. FMD-endemic regions typically organize vaccination campaigns as a routine preventive control policy or to mitigate the impact of the disease. The majority of currently used vaccines are formulated with chemically inactivated whole-viral particles and suitable adjuvants such as single and double oil emulsions. The most recent strains circulating in a particular region are typically selected as antigens based on the results of vaccine-matching data and in vitro experiments, however, predictions based on vaccine-matching approaches are usually uncertain without a live virus challenge in natural hosts combined with reliable field data. Vaccine selection and successful vaccination campaigns rely on a deep knowledge of the epidemiology of the region where these vaccines will be used, as well as access to the appropriate diagnostic tools to underpin these campaigns.